2004
DOI: 10.1007/s00256-004-0830-6
|View full text |Cite
|
Sign up to set email alerts
|

The arthropathy of systemic sclerosis: a 12 month prospective clinical and imaging study

Abstract: This cross-sectional prospective study confirms that an arthropathy is common in SSc patients and shows that it is a major determinant of disability. A classification of radiological alterations into three specific patterns is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
63
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 16 publications
21
63
1
2
Order By: Relevance
“…They may appear years before clinical onset of arthritis and are considered highly sensible and specific for RA. In this decade, anti-CCP has evolved from being a diagnostic tool to a biological marker which allows understanding of the pathogenetic features of RA [2]. Also, it has been observed that anti-CCP positive RA occurs mainly in patients with shared-epitope alleles and characterizes more aggressive disease with higher radiological degree of joint destruction [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may appear years before clinical onset of arthritis and are considered highly sensible and specific for RA. In this decade, anti-CCP has evolved from being a diagnostic tool to a biological marker which allows understanding of the pathogenetic features of RA [2]. Also, it has been observed that anti-CCP positive RA occurs mainly in patients with shared-epitope alleles and characterizes more aggressive disease with higher radiological degree of joint destruction [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal involvement is seen in 24-97% of the patients [1,2] and may present with arthritis, arthralgias, joint contractures, tenosynovitis, muscle atrophy and loss of joint function [3]. A symmetrical polyarthritis similar to rheumatoid arthritis (RA) can also be found characterizing an SSc-RA overlap syndrome [4].…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic studies in SSc and RA have shown that the commonly affected areas are the joints, soft tissue, and bones of the hands [13,14,[17][18][19]. However, radiographs exhibit some limitations regarding their sensitivity to detect early inflammatory changes, such as effusion or synovitis, and they cannot assess tendon damage.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding systemic sclerosis (SSc), joint symptoms are reported by 24-97% of SSc patients during the course of their disease, and are frequently disabling [12][13][14][15][16]. Manifestations of SSc hand are ranging from arthralgias to frank arthritis, contractures, and tendon friction rubs [12].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanism of arthritis resulting in cricoatytenoid joint fixation in scleroderma resembles RA. The synovium is infiltrated by lymphocytes and plasma cells, and fibrin deposits in the joint space lead to fibrous ankylosis [31].…”
Section: Discussionmentioning
confidence: 99%